No country is self-sufficient when it comes to plant genetic resources for food and agriculture: the cases of Bhutan, Burkina Faso, Costa Rica, Côte d’Ivoire, Guatemala, Nepal, Rwanda and Uganda - Vernooy, Ronnie; Clancy, Evelyn (Bioversity International, 2017)
This brief aims to create more awareness that no country is self-sufficient in plant genetic resources and that international exchanges have facilitated critical variety innovations in individual countries contributing significantly to agricultural productivity enhancement. The brief synthesizes eight national country studies on the interdependence and flow of plant genetic resources (or the dynamics of the global crop commons) carried out under the umbrella of the project Strengthening National Capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture coordinated by Bioversity International.